Sustainable development and Islamic philanthropy: Synergy of zakat and SDGs - Arwani, Agus; Muhammad, Rifqi; Mahmudi, Mahmudi (al-Uqud : Journal of Islamic Economics, 2024)
The research aims to explore the synergy between Zakat as a form of Islamic philanthropy and the Sustainable Development Goals (SDGs), which include economic, social and environmental dimensions, to meet the needs of the current generation without compromising the capabilities of future generations. Using a Systematic Literature Review (SLR) approach, this research analyses relevant literature to understand the potential and obstacles to integrating Zakat with sustainable development. Research findings show that Zakat can accelerate poverty alleviation, improve access and quality of education, and fund health programs which align with several SDG targets. However, challenges faced in zakat integration include less positive public perceptions, regulations that still need optimisation, and gaps in zakat management practices. The implications of these findings show that to optimise Zakat's contribution to achieving the SDGs, increased governance, transparency, and cross-sector collaboration are needed. This research provides valuable insights for policymakers, zakat practitioners, and other interested parties to design more effective strategies for utilising Zakat as the primary driver of achieving the SDGs.